Philosophical Logic - Arrington, Robert L. author. aut Link
VIII, 162 p.
Keywords: With this issue we initiate the policy of expanding the scope of Tulane Studies in Philosophy to include, in addition to the work of members of the department, contributions from philosophers who have earned advanced degrees from Tulane and who are now teaching in other colleges and universities. The Editor THE LOGIC OF OUR LANGUAGE ROBERT L. ARRINGTON Wittgenstein wrote in the Tractatus that "logic is not a body of doctrine, but a mirror-image of the world. " 1 In line with his suggestion that a proposition is a 'picture', Wittgenstein argued that propositions 'show' the logical structure of the real. He was insistent, however, that "the apparent logical form of a proposition need not be its real one. " 2 As a result of this we can misunderstand the structure of fact. Philosophical problems arise just when "the logic of our language is mis understood. " 3 It is common knowledge that much of this view of logic was rejected by Wittgenstein himself in the Philosophical Investi gations. There we are told that language has no ideal or sublime 4 logic which mirrors the structure of the extra-linguistic world. Consequently, inferences from the structure of language to the structure of that extra-linguistic world are invalid. Reality can be 'cut up' in any of a number of ways by language. Wittgenstein adopted a view of philosophy which would render that discipline a non-explanatory, non-critical study of the multiple ways in which language can be used.